VIRAL MARKETING MESSAGE, CONSUMERS’ ATTITUDE TOWARDS VIRAL MARKETING, COMPETITIVENESS ABILITY, AND BUSINESS PERFORMANCE - Trixie Nova Bella Tandijaya; Samuel Hatane (Jurnal Manajemen Pemasaran, 2021)
Empowerment of technology and the use of digital media that are currently practiced through appropriate marketing strategies and tactics will be able to make businesses survive in the midst of the Covid-19 pandemic. Viral marketing strategy is a low-cost effective marketing strategy for mass targeting. Powerful viral promotions can reach thousands of consumers, can inspire them to buy certain branded products, and create a competitive advantage for businesses. This study takes the Tanggulangin leather craft SMEs as one of the centers of the leather industry in Indonesia, with the research variables being viral marketing message strategies, consumer attitudes towards viral marketing, competitiveness ability, and business performance. The study was conducted on 235 respondents who met the requirements of the research provisions. Data analysis using SmartPLS 3. The results obtained are that viral marketing massage has a direct positive effect on consumer attitudes towards viral marketing, competitiveness, and business performance. Consumer attitudes towards viral marketing have a direct positive effect on competitiveness and business performance. In addition, consumer attitudes towards viral marketing partially mediate the relationship between viral marketing messages and competitiveness, and competitive ability partially mediates the relationship between consumer attitudes towards viral marketing and business performance.